Stimuli-responsive drug delivery nanocarriers in the treatment of breast cancer - Oshiro-Júnior, João A. [UNESP]; Rodero, Camila [UNESP]; Hanck-Silva, Gilmar [UNESP]; Sato, Mariana R. [UNESP]; Alves, Renata Carolina [UNESP]; Eloy, Josimar O.; Chorilli, Marlus [UNESP] (Bentham Science Publishers, 2020)
Stimuli-responsive drug-delivery nanocarriers (DDNs) have been increasingly reported in the literature as an alternative for breast cancer therapy. Stimuli-responsive DDNs are developed with materials that present a drastic change in response to intrinsic/chemical stimuli (pH, redox and enzyme) and extrinsic/physical stimuli (ultrasound, Near-infrared (NIR) light, magnetic field and electric current). In addition, they can be developed using different strategies, such as functionalization with signaling molecules, leading to several advantages, such as (a) improved pharmaceutical properties of liposoluble drugs, (b) selectivity with the tumor tissue decreasing systemic toxic effects, (c) controlled release upon different stimuli, which are all fundamental to improving the therapeutic effectiveness of breast cancer treatment. Therefore, this review summarizes the use of stimuli-responsive DDNs in the treatment of breast cancer. We have divided the discussions into intrinsic and extrinsic stimuli and have separately detailed them regarding their definitions and applications. Finally, we aim to address the ability of these stimuli-responsive DDNs to control the drug release in vitro and the influence on breast cancer therapy, evaluated in vivo in breast cancer models.
Keywords: Breast cancer treatment; Extrinsic/physical stimuli; Intrinsic/chemical stimuli; Liposoluble drugs; Near-infrared light (NIR); Stimuli-responsive drug delivery nanocarriers